PENGARUH LABELISASI HALAL TERHADAP KEPUTUSAN MASYARAKAT KECAMATAN PERBAUNGAN DALAM PEMBELIAN PRODUK MAKANAN DALAM KEMASAN - Ady Syahputra; Haroni Doli Hamoraon (Departemen Ekonomi Pembangunan USU, 2014)
Perbaungan is one of sub-district in the regency of Serdang Bedagai. Major population of Perbaungan is Muslim. Which is 104.979 people or 92,50% from the whole number in the sub-district, it is 113.490 people. This research is limited to Muslim’s perception, the purpose of this research is to know how the perception of people in Perbaungan about the food in packaging. And to know how the label halal of that food effect.In addition, the object of the research is the society, especially Muslim in Perbaungan who are consist of various professions. The data of this research is the primary data which is collected by the questionnaire which is given to the respondents. The sample is 60 respondents with Non probability sampling. The research is the descriptive analysis. That is researcher has to do the tabulation of data by using likert’s scale.The result shows that Halal label product is well known for the people of Perbaungan. And the other result is labeling halal logo can be significant impact for the people’s buying decision.Keyword : perception, perbaungan’s people, and halal labeling.